Antonio Boaventura da Silva: o professor e suas concepções sobre a educação física nas décadas de 1940-1970 - Lourdes, Luiz Fernando Costa de (2007)
This study is aimed at the comprehension of professor Antonio Boaventura da Silva's ideas on Physical Education and pedagogical practices as director of the technical division of the Department of Physical Education and Sports and as instructor of General Physical Education and Gymnastics at the State Physical Education College of São Paulo between 1940 and 1970. Based on hystorichal sources af the personnal archives of Boaventura. For such, both da Silva's professional formation and actions through his carrier are analyzed, as well as the different international models of pedagogical practices on which he based his own practices